Functional Redundancy and Complementarities of Seed Dispersal by the Last Neotropical Megafrugivores - Bueno, Rafael S. [UNESP]; Guevara, Roger; Ribeiro, Milton C. [UNESP]; Culot, Laurence [UNESP]; Bufalo, Felipe S. [UNESP]; Galetti, Mauro [UNESP] (Public Library of Science (PLoS), 2013)
Background: Functional redundancy has been debated largely in ecology and conservation, yet we lack detailed empirical studies on the roles of functionally similar species in ecosystem function. Large bodied frugivores may disperse similar plant species and have strong impact on plant recruitment in tropical forests. The two largest frugivores in the neotropics, tapirs (Tapirus terrestris) and muriquis (Brachyteles arachnoides) are potential candidates for functional redundancy on seed dispersal effectiveness. Here we provide a comparison of the quantitative, qualitative and spatial effects on seed dispersal by these megafrugivores in a continuous Brazilian Atlantic forest. Methodology/Principal Findings: We found a low overlap of plant species dispersed by both muriquis and tapirs. A group of 35 muriquis occupied an area of 850 ha and dispersed 5 times more plant species, and 13 times more seeds than 22 tapirs living in the same area. Muriquis dispersed 2.4 times more seeds in any random position than tapirs. This can be explained mainly because seed deposition by muriquis leaves less empty space than tapirs. However, tapirs are able to disperse larger seeds than muriquis and move them into sites not reached by primates, such as large forest gaps, open areas and fragments nearby. Based on published information we found 302 plant species that are dispersed by at least one of these megafrugivores in the Brazilian Atlantic forest. Conclusions/Significance: Our study showed that both megafrugivores play complementary rather than redundant roles as seed dispersers. Although tapirs disperse fewer seeds and species than muriquis, they disperse larger-seeded species and in places not used by primates. The selective extinction of these megafrugivores will change the spatial seed rain they generate and may have negative effects on the recruitment of several plant species, particularly those with large seeds that have muriquis and tapirs as the last living seed dispersers. © 2013 Bueno et al.
Keywords: controlled study; forest fragmentation; forest structure; frugivore; muriqui; Neotropics; nonhuman; plant dispersal; plant leaf; qualitative research; quantitative study; redundancy analysis; seed dispersal; seed size; species comparison; tapir; Animals; Atelinae; Brazil; Cryptocarya; Ecological and Environmental Processes; Ferns; Germination; Herbivory; Perissodactyla; Seed Dispersal; Spatial Analysis; Trees